2015
DOI: 10.3390/nu7105422
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Fatigue and Antioxidant Activity of the Polysaccharides Isolated from Millettiae speciosae Champ. Leguminosae

Abstract: Millettiae speciosae Champ. Leguminosae (MSC), is a well-known Chinese herb traditionally used as food material and medicine for enhancing physical strength. Our preliminary study found that the aqueous extract of this herb (MSE) had an anti-fatigue effect. In this paper, we further separated MSE into total polysaccharides (MSP) and supernatant (MSS) by alcohol precipitation, and explored which fraction was active for its anti-fatigue effect. Mice were orally administered with MSP or MSS at the doses of 200, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 28 publications
2
32
0
Order By: Relevance
“…As cytosolic enzymes, LDH and CK are physiologically abundant in organs' cells (e.g., heart, kidney, and skeletal muscles). However, during the process of exhaustive exercise, excessive ROS causes muscle cell damage, which increases LDH and CK in the blood [6]. The data from the present study showed that PPO significantly decreased serum LDH and CK levels of mice, implying that PPO had a preventive effect on exercise-induced muscle damage.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…As cytosolic enzymes, LDH and CK are physiologically abundant in organs' cells (e.g., heart, kidney, and skeletal muscles). However, during the process of exhaustive exercise, excessive ROS causes muscle cell damage, which increases LDH and CK in the blood [6]. The data from the present study showed that PPO significantly decreased serum LDH and CK levels of mice, implying that PPO had a preventive effect on exercise-induced muscle damage.…”
Section: Discussionsupporting
confidence: 46%
“…The principal non-enzymic antioxidants include reduced glutathione (GSH), vitamin C, and vitamin E [5]. An imbalance can be produced by exhaustive exercise in ROS and antioxidant defense, which results in oxidative stress [6]. This harmful status may lead to oxidative damage in all cellular components, including proteins, nucleic acids, lipids, and carbohydrates [7].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the comparison of the above results, it was found that in the five antioxidant test, PEP had significantly higher antioxidant activity than other polysaccharides in reducing power, DPPH, superoxide anion radical and ABTS. In addition, it was reported that there was a strong positive correlation between antioxidant activity and anti‐fatigue activity (Zhao et al , ; Zhao et al , ; Ma et al , ), so we chose PEP with the best antioxidant activity to further study the anti‐fatigue activity in mice.…”
Section: Resultsmentioning
confidence: 99%
“…The total polysaccharides (DOP) and supernatant (DOS) of D. officinale were prepared as previously described (Lin, Shaw, Sze, Tong, & Zhang, 2011;Zhao et al, 2015). Briefly, D. officinale (100 g) was fractured into pieces and extracted three times with boiling water (1:20, wt/wt) for 2.5 h. The combined extracts were centrifuged to remove impurities.…”
Section: Preparation Of Dop and Dos From D Officinalementioning
confidence: 99%